Uji Organoleptik Penambahan Jus Buah Jambu Biji Merah (Psidium guajava Linn) Terhadap Tingkat Kesukaan Responden Pada Yoghurt Susu Kambing Etawa - Noer Sarifah Ainy; Windi Lediawati; Nestiyanto Hadi (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Goat's milk has a distinctive aroma and taste, a strong aroma and even the aroma of the goat's body sticks to the milk produced, and the taste is more savory, this is why many people don't like goat's milk even though goat's milk is better in nutritional content than goat's milk. Cow's milk and goat's milk are not prone to causing allergies when consumed by both children and the elderly, in this study using red guava fruit juice (Psidium guajava Linn) as a mixture of Etawa crossbreed goat milk yogurt with different concentrations of 23.0%, 28.5%, and 33.3%. The main purpose of this study was to determine the respondent's level of preference for Etawa crossbreed goat's milk yogurt. The method in this study uses a quantitative descriptive method with a one way ANOVA approach. The sample in this study were visitors to the D'kandang educational tourism park, the Amazing white sand Farm of Sawangan, Depok, which amounted to 30 people. The sampling technique used is simple random sampling technique, the instrument used is a questionnaire. Yogurt with the addition of red guava fruit juice as much as 23.0%, 28.5%, and 33.3% had an effect on the level of preference of respondents. It can be concluded that there is a significant effect on the aroma, taste and level of respondent's preference for the yogurt produced.